Determination of methenamine residues in edible animal tissues by HPLC-MS/MS using a modified QuEChERS method: Validation and pilot survey in actual samples. (March 2016) - Xu, Xing; Zhang, Xiaoming; Duhoranimana, Emmanuel; Zhang, Yan; Shu, Ping
Abstract: A modified QuEChERS (quick, easy, cheap, effective, rugged, and safe) method was developed for the determination of methenamine in edible animal tissues by high performance liquid chromatography coupled with tandem mass spectrometry (HPLC-MS/MS). Samples were extracted with acetonitrile, and cleaned with anhydrous sodium sulfate and primary secondary amine (PSA) sorbent. An isotope dilution mass spectrometry technique was applied to compensate for matrix effect. The separation was performed on a HILIC column, and the mobile phase composed of acetonitrile-0.1% of formic acid and 5.0 mmol/L of ammonium acetate in water. The method showed a linear relationship in the range of 1.0–20.0 μg/L for methenamine, and the determination coefficients ( R 2 ) ranged from 0.9939 to 0.9995. The limit of detection (LOD) and quantification (LOQ) for methenamine in animal tissues sample was 1.5 μg/kg and 5.0 μg/kg, respectively. The average recoveries were 86.7–109.5% at spiked levels of 5.0, 25.0, 100.0 μg/kg. The intra-day precision ranged from 2.6 to 7.0%, and the inter-day precision ranged from 4.9 to 11.3%. The validated method was successfully applied to determination of methenamine in swinish muscle, kidney and liver. Highlights: QuEChERS is a rapid and convenient method for determining the methenamine. Pretreatment process was developed to extract and purify methenamine in edible animal tissues. The possible mechanism of the salts and sorbents in methenamine was discussed.